(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
In this article we are analize the separate aspects of the character of Venko Markovski, the first contemporary Macedonian poet, the member in the National-Liberation War, the supporter of Stalin and the national dissident. Because of the subject and the several difficult explanations about the character of Markovski, we will write only about the so called Macedonian chapter of his activities. We will write only about his membership in the National-Liberation War, until his immigration in Republic of Bulgaria. We will try to explain, what is the reason of the transformation of Venko Markovski.